Strategi Komunikasi Mahasiswa Perantau Menghadapi Culture Shock di Kota Medan - Jihan Syalwa; Anang Anas Azhar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to analyze the communication strategies used by migrant students in dealing with culture shock in Medan City. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The informants consisted of five students from various regions in Sumatra who were studying at UINSU and UMSU. The results of the study showed that the communication style of Medan people is loud, expressive, and direct triggers culture shock. To overcome this, students apply accommodative communication strategies, are active in campus social activities, build social support networks, and utilize social media as a means of adaptation. Environmental support and mental readiness play an important role in the adjustment process. These findings are relevant to the Communication Accommodation Theory and intercultural communication, and recommend the need for a cultural adaptation assistance program for migrant students in the campus environment.